Antibacterial performance of various amine functional polymers coated silica nanoparticles. (28th January 2016) - Lee, Inkyu; Roh, Jongmin; Lee, Jungsup; Song, Jooyoung; Jang, Jyongsik
Abstract: Five types of amine functional polymer shells were formed on the surface of silica nanoparticles via vapor deposition polymerization and oxidation polymerization. Scanning electron microscopy, transmission electron microscopy, elemental analysis, and Fourier transform infrared spectroscopy have been used to characterize the resulting various types of amine functional polymers coated silica nanoparticles. Electron microscopy studies reveal that the thin polymer shell is successfully formed on the silica surface. The antibacterial performance of the prepared core/shell nanoparticles was investigated against both Gram-positive ( Escherichia coli ) and Gram-negative ( Staphylococcus aureus ) bacteria. The various amine functional polymers coated silica nanoparticles presented antibacterial activity against both bacteria. In contrast, silica/PPy core/shell nanoparticles had no bactericidal efficiency, because the amine group of PPy does not provide protonated nitrogen atoms which can kill the bacteria. The obtained results evidence that antimicrobial activity of amine functional polymers is influenced by the state of the amine groups than positively charged amino groups. Graphical abstract: Highlights: We fabricated five different amine functional polymer coated silica with a simple method. We investigated comparatively antibacterial activities of five different core/shell nanoparticles. The core/shell nanoparticles provide dependency of the antibacterial properties on the state of amine groups.